Long-term liver deportalisation in stable and time prolonged prehepatic portal hypertension model affects expression of hypoxia, angiogenesis, apoptosis, and autophagy markers in the young rats’ liver - Godik , Oleg (The Ukrainian Scientific Medical Youth Journal, 2024)
prehepatic portal hypertension in children cause severe and life-threatening complications, that highlights the need in in-depth investigations of pathogenetic mechanisms, which contribute to prehepatic portal hypertension-associated liver pathology. In developed stable experimental prehepatic portal hypertension model in adolescent rat males we aimed to assess the expression levels of the key molecular markers of hypoxia, angiogenesis, autophagy, and apoptosis in the liver tissue after 6-month deportalization. Partial portal vein ligation was performed in 4-week old male rats. After 6-months tissue samples from PHP-model, sham operated and control animals were studied by western blot to identify protein levels of markers related to prehepatic portal hypertension -induced liver injury. Partial portal vein occlusion upregulated hypoxia inducible factor -1α (by 4.67 folds vs. control, p<0.001) and vascular endothelial growth factor protein expression levels (by 2.33 folds vs. control, p<0.001) suggesting chronic hypoxia development. Abnormally high levels of angiostatin isoforms were found (by 9.88 folds vs. control, p<0.001) to signify angiogenesis dysregulation. Significant caspase-3 (23.4-fold increase vs. control, p<0.001) overexpression is executive phase of apoptotic cell death evidence. Dramatic LC3 level expression indicates existence of crosstalk between autophagy and apoptosis that contribute to fibrotic changes. Hypoxia-induced events, impaired angiogenesis regulation, enhanced autophagy and apoptosis are contributing factors of prehepatic portal hypertension -induced liver injury. A better understanding of subtle molecular mechanisms of this pathology may pave the way for innovative treatment options.